Percutaneous endoscopic gastrostomy - Xudong Liu; Zhengqiang Yang; Shun He; Guiqi Wang (Society of Gastrointestinal Intervention, 2021)
Percutaneous endoscopic gastrostomy (PEG) is a feasible and safe technique for patients who need long-term feeding and cannot eat orally. With the increasing maturity of PEG technique, a large number of patients receive PEG tube placement every year in the world. However, PEG tube placement is not necessary in some patients, and some other patients are not evaluated strictly, leading to serious complications. In a broad sense, the mainly two indications for PEG include long-term enteral nutrition and gastric decompression. On the other hand, the main contraindications of PEG are distal intestinal obstruction, severe coagulation abnormalities, and severe infection at the PEG site. In the first section of this review, the indications and contraindications of PEG are introduced. Although PEG tube placement is a relatively safe technique, it can still cause a number of complications, including minor and major complications. Through standard management and treatment, the outcome of most patients is very good. In the second section of this review, we describe a variety of minor and major tube-related complications, and the treatment and prevention of these complications. In addition, the preparation and post-insertion care are also very important for PEG, which can reduce the incidence of complications. In the last section of this review, we describe related issues about the preparation and post-insertion care of PEG. In conclusion, PEG tube placement is a widely accepted technique that can bring benefits to the right patients.